Simulation Model Application to Predict the Effect of Salinity on Surfactant Adsorption and Retention in Alkali Surfactant Flooding - Muhammad Taufiq Fathaddin; Rachmat Sudibjo; Kartika Fajarwati H.; Shabrina Sri Riswati (Journal of Earth Energy Science, Engineering, and Technology, 2019)
Modeling works of alkali surfactant injection are presented in this paper, in order to analysis the effect of salinity on surfactant adsorption and retention. Simulation model was built using UTCHEM simulator. The simulation model was validated using laboratory experiment. From the laboratory experiment and modeling, it was found that surfactant retention, as well as surfactant adsorption, increased with the salinity. However they were not linearly related. The application of microemulsion Type III (salinity of 1.4% wt.) gave the optimum flooding. Although more surfactant was adsorbed and retained compared to microemulsion Type I (salinity of 1.4% wt.), but it yielded the highest recovery factor. The formation of microemulsion Type II (salinity of 2.0% wt.) should be avoided since it effectively caused surfactant loss due to surfactant adsorption and retention.